HUBUNGAN DAYA TAHAN DAN KECEPATAN TERHADAP HASIL LARI 800 METER PUTRA PADA ATLET ATLETIK PASI RIAU - M Saputra '; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the problem in this research is at the moment in the event because it is no longer able to increase the speed of 150 past so that there is a difference this time. Athletes suspected problem less endurance and speed are less than the maximum so that the result would not achieve peak performance. This study aims to Determine Whether there is a correlation with the endurance and speed of 800m athletics results PASI Riau. sample in this study was a athlete athletics PASI Riau many as 6 people. From the calculation of the correlation between endurance (X1) with the result a run 800m (Y) is obtained that r calculation = 0,965 while r tabel= 0,811 with degree α = 0,05. it can be concluded that there is significant correlation between endurance with the results of run 800m. then the result of calculation of correlation between the speed (X2) with the result a run 800m (Y) is obtained r calculation= 0.956 while r tabel= 0.811 degree α = 0,05. it can be concluded that there is significant correlation  between speed with the results of run 800m, Afterwards the result from the calculation of double correlation (R test) is obtained that Rcalculation = 0.960 while Rtabel = 0,811 so, Rcalculation > Rtabel, and it’s mean there is a significant corelation between Endurance (X1) and speed (X2) the results a run 800m (Y). Key words: Endurance,  Speed,  Results A Run 800m